ANALISIS YURIDIS TERKAIT PIDANA PENGGELAPAN SERTIFIKAT HAK MILIK: STUDI PUTUSAN NOMOR 253/PDT.G/2020/PN BYW DALAM KASUS PERUMAHAN GARUDA REGENCY BANYUWANGI - Ramires, Moch. Faschal; Lyanthi, Merline Eva (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This research discusses a case of breach of duty by a notary (Defendant I) who failed to complete the certificate transfer process and handed over the certificate to another party without the plaintiff’s consent as the collateral holder. The actions fulfill the elements of unlawful acts (Article 1365 of the Civil Code) and embezzlement (Article 372 of the Criminal Code) due to the abuse of trust. As a public official, the notary should uphold the legal interests of both parties in accordance with the Notary Public Office Law (UUJN), but in this case, there was a violation of the principles of honesty, independence, and impartiality. The judge ruled that the notary, along with the other parties (Defendants II and III), is responsible for compensating the plaintiff’s losses. The material losses suffered by the plaintiff, including the delay of a project worth Rp7.5 billion, demonstrate the significant impact of this violation. The ruling reflects the principles of legal certainty and justice by punishing the party that violated the law. This study highlights the importance of strict supervision of the notary profession to maintain its integrity and emphasizes that notaries can be held civilly and criminally liable for violations of their duties and obligations